2018
DOI: 10.1186/s12884-018-1984-x
|View full text |Cite
|
Sign up to set email alerts
|

The effect of advanced maternal age on perinatal outcomes in nulliparous singleton pregnancies

Abstract: BackgroundPregnancy at advanced maternal age has become more common in both developed and developing countries over the last decades. The association between adverse perinatal outcomes and advanced maternal age has been a matter of controversy in several studies. The objective of this study is to investigate the impact of advanced maternal age on perinatal and neonatal outcomes of nulliparous singleton pregnancies.MethodsRecords of patients admitted to the Department of Obstetrics and Gynecology, University of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

18
107
7
8

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 159 publications
(164 citation statements)
references
References 21 publications
18
107
7
8
Order By: Relevance
“…13 In two recent studies that, like ours, defined AMA as being over 40 years, AMA was associated with gestational diabetes and cesarean delivery but the rate of preterm birth and stillbirth were not increased, as in our study. 14,15 In another large multi-country survey by Laopaiboon et al, 16 involving over 350 health facilities in 29 countries across the world, AMA was associated with composite adverse maternal and perinatal outcome. In the present study, however, AMA was not associated with increased adverse perinatal outcomes such as preterm birth, stillbirth, or NICU admission.…”
Section: Discussionmentioning
confidence: 99%
“…13 In two recent studies that, like ours, defined AMA as being over 40 years, AMA was associated with gestational diabetes and cesarean delivery but the rate of preterm birth and stillbirth were not increased, as in our study. 14,15 In another large multi-country survey by Laopaiboon et al, 16 involving over 350 health facilities in 29 countries across the world, AMA was associated with composite adverse maternal and perinatal outcome. In the present study, however, AMA was not associated with increased adverse perinatal outcomes such as preterm birth, stillbirth, or NICU admission.…”
Section: Discussionmentioning
confidence: 99%
“…AMA in humans is an established risk factor for the development of an array of pregnancy-induced pathologies 6, 8, 26, 38, 39 . While the relationship between maternal age and the incidence of pregnancy-related pathologies exists, pre-clinical models with similar reproductive physiology to that of humans are severely lacking.…”
Section: Discussionmentioning
confidence: 99%
“…These findings indicate that the vervet monkey recapitulates some, but not all aspects of altered BP regulation during pregnancy in older mothers. Gaillard et al indicated that a woman’s maternal age per se was not consistently correlated with gestational hypertension, and that maternal body mass index might influence alterations in BP regulation during pregnancy 38 . In fact, maternal obesity has been shown to interact with maternal age to promote a variety of other pregnancy-induced pathologies 38 .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations